PENERAPAN SANKSI PIDANA BAGI ANAK PELAKU TINDAK PIDANA PENGANIAYAAN DI PENGADILAN NEGERI KELAS IA SAMARINDA BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 - Apriyani Damai Yanti (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT his study aims to find out what that factor into consideration Judges and the Government's efforts to protect children who are victims of crime. Kids should be seen as a valuable asset of the Nation in the future which should be preserved and protected their rights. Legal protection for children can be interpreted as an effort to legal protection of the freedoms and rights of children as well as the various interests related to child welfare. Lately phenomena that occur in the community showed criminal offenses committed by children increased from time to time, as often reported in the media both print and electronic media about the events of that crime perpetrators are children.The basic problem in the sentencing of children is an adverse effect of punishment on child development, criminal acts committed by children is similar to acts committed by adults, the difference lies in the principal culprit is done by children. But the age limit is usually used to benchmark the extent to which children can be accounted against crime. Based on Article 45 of the Criminal Code can we mentioned that the definition of a child is not yet 16 years old. Criminal sanctions and measures imposed on children who commit criminal acts in particular Article 23 and Article 24 of Law No. 11 of 2012 on Child Criminal Justice.Method The approach taken in this study is a juridical empirical research data collection techniques derived Writer based research in the field and library research or analysis of the articles of the Regulation Legislation governing theses problems. Therefore, in carrying out the examination of the child as a criminal, it must be noted about the purpose of Juvenile Justice. That is make corrections and rehabilitation, so that the child can come back to life normal and independent for the sake of its future potential. Keywords        : the Child Protection Law, Law Number 11 Year 2012 About Child Criminal Justice     System.